Modeling the Field Value Variations and Field Interactions Simultaneously for Fraud Detection - Xi, Dongbo; Song, Bowen; Zhuang, Fuzhen; Zhu, Yongchun; Chen, Shuai; Zhang, Tianyi; Qi, Yuan; He, Qing (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
With the explosive growth of e-payment industry, online transaction fraud has become one of the biggest challenges for the business. The historical behavior information of users provides rich information for digging into the users' fraud risk. While considerable efforts have been made in this direction, a long-standing challenge is how to effectively exploit user's behavioral information and provide explainable prediction results. In fact, the value variations of same field from different events and the interactions of different fields within one event have proven to be strong indicators of fraudulent behaviors. In this paper, we propose the Dual Importance-aware Factorization Machines (DIFM), which exploits the inter- and intra-event information among users’ behavior sequence from dual perspectives, i.e., field value variations and field interactions simultaneously for fraud detection. The proposed model is deployed in Alipay's risk management system, which provides real-time fraud detection service for e-commerce platforms. Experimental results on industrial data under various scenarios in the platform clearly demonstrate that our model achieves significant improvements compared with various state-of-the-art baseline models. Moreover, the \model~could also give an insight into the explanation of the prediction results from dual perspectives.